Low Doses of Psilocybin and Ketamine Enhance Motivation and Attention in Poor Performing Rats: Evidence for an Antidepressant Property - Higgins, Guy A.; Carroll, Nicole K.; Brown, Matt; MacMillan, Cam; Silenieks, Leo B.; Thevarkunnel, Sandy; Izhakova, Julia; Magomedova, Lilia; DeLannoy, Ines; Sellers, Edward M. (Frontiers in Pharmacology, 2021)
Long term benefits following short-term administration of high psychedelic doses of serotonergic and dissociative hallucinogens, typified by psilocybin and ketamine respectively, support their potential as treatments for psychiatric conditions such as major depressive disorder. The high psychedelic doses induce perceptual experiences which are associated with therapeutic benefit. There have also been anecdotal reports of these drugs being used at what are referred to as “micro” doses to improve mood and cognitive function, although currently there are recognised limitations to their clinical and preclinical investigation. In the present studies we have defined a low dose and plasma exposure range in rats for both ketamine (0.3-3 mg/kg [10-73 ng/ml]) and psilocybin/psilocin (0.05-0.1 mg/kg [7-12 ng/ml]), based on studies which identified these as sub-threshold for the induction of behavioural stereotypies. Tests of efficacy were focussed on depression-related endophenotypes of anhedonia, amotivation and cognitive dysfunction using low performing male Long Evans rats trained in two food motivated tasks: a progressive ratio (PR) and serial 5-choice (5-CSRT) task. Both acute doses of ketamine (1-3 mg/kg IP) and psilocybin (0.05-0.1 mg/kg SC) pretreatment increased break point for food (PR task), and improved attentional accuracy and a measure of impulsive action (5-CSRT task). In each case, effect size was modest and largely restricted to test subjects characterised as “low performing”. Furthermore, both drugs showed a similar pattern of effect across both tests. The present studies provide a framework for the future study of ketamine and psilocybin at low doses and plasma exposures, and help to establish the use of these lower concentrations of serotonergic and dissociative hallucinogens both as a valid scientific construct, and as having a therapeutic utilty.